2020
DOI: 10.3390/cells9030545
|View full text |Cite
|
Sign up to set email alerts
|

Optical Tweezers in Studies of Red Blood Cells

Abstract: Optical tweezers (OTs) are innovative instruments utilized for the manipulation of microscopic biological objects of interest. Rapid improvements in precision and degree of freedom of multichannel and multifunctional OTs have ushered in a new era of studies in basic physical and chemical properties of living tissues and unknown biomechanics in biological processes. Nowadays, OTs are used extensively for studying living cells and have initiated far-reaching influence in various fundamental studies in life scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 158 publications
(259 reference statements)
0
64
0
Order By: Relevance
“…Recently, the active nature of RBC flickering was investigated using active and passive microrheology of a single RBC in a sophisticated four-bead OT configuration [ 21 ]. The advances in OT technology, such as multiple and dynamic optical traps and circular to linear light polarization in OTs, allowed for multiple applications in studies of RBCs, as also shown in two recent reviews [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the active nature of RBC flickering was investigated using active and passive microrheology of a single RBC in a sophisticated four-bead OT configuration [ 21 ]. The advances in OT technology, such as multiple and dynamic optical traps and circular to linear light polarization in OTs, allowed for multiple applications in studies of RBCs, as also shown in two recent reviews [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the relevant studies have been provided by under in-vitro conditions (Ben-Ami et al, 2003 ; Relevy et al, 2008 ; Barshtein et al, 2018 ; Lee et al, 2018 ; Zaninoni et al, 2018 ; Zhu et al, 2020 ), but Jani et al estimate the erythrocyte mechanical properties in-vivo during capillary plug flow. To characterize the mechanical properties of red blood cells, the authors ( Jani et al ) combined the capabilities of intravascular microscopy with numerical simulation.…”
Section: Methods For Characterization Of Rbcs Flow-affecting Propertimentioning
confidence: 99%
“…Spectrum of in-vitro techniques that can be used for characterization of RBCs flow-affecting properties is very broad. This list includes laser ektacytometry ( Semenov et al ; Lee et al ), laser tweezers (Lee et al, 2018 ; Zhu et al, 2020 ), atomic force microscopy (Steffen et al, 2013 ), microfluidics (Ben-Ami et al, 2003 ; Relevy et al, 2008 ; Guo et al, 2016 ; Barshtein et al, 2018 ; Lee et al, 2018 ; Lim et al, 2018 ). In this Research Topic, Depond et al discuss the usefulness of these methods for the characterization of the RBC deformability for malaria patients.…”
Section: Methods For Characterization Of Rbcs Flow-affecting Propertimentioning
confidence: 99%
“…In recent years, researchers also proposed the optical trapping [ 16 , 17 ] or sorting [ 18 ] through optical waveguides, which offers a new approach for single cell or bacterial study. With the in-depth development of research, the combined application of optical tweezers and other technologies has extended to more new research fields, which effectively promotes the development in the fields of life science, material science, physics, chemistry, medicine, and nanotechnology [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%